A Comprehensive Framework for Future Road Safety Strategies - Hughes, Brett Peter (Curtin University, 2017)
Internationally, road fatalities and injury are a massive public health, social, economic and transport problem that road safety strategies are developed to counteract. This thesis aimed to investigate and improve the applicability, responsiveness, efficiency and effectiveness of these strategies. A comprehensive and coherent framework, comprising nine mutually interacting Components, with 75 subcomponents, that contribute to crashes, and ten generic Policy Tools, was developed. The framework is based on safety and system theory, principles and practice.